- PELATIHAN DESAIN GRAFIS UNTUK MENINGKATKAN KREATIVITAS SISWA KERJA LAPANGAN MENGGUNAKAN SOFTWARE ADOBE ILLUSTRATOR CC 2020: - - Alkodri, Ari Amir; Andrika, Yuyi; Mayasari, Melati Suci; Saftari, Maya; Adiwinoto, Bambang (ISB Atma Luhur, 2025)
The increase in the need for workers is very rapid if not prepared, it will result in a lot of unemployment. The problem of unemployment at the level of vocational high school graduates who do not continue their studies cannot be handled effectively, resulting in economic and social disparities. Therefore, it is necessary to improve the steps for developing the workforce, especially for vocational high school students who are carrying out PKL (field work practice) that is in accordance with the needs of the workforce, including through work training that is strongly supported by the supervising teacher, Head of DKV Department and the respective schools. With this graphic design training, participants in the vocational high school PKL training are expected to be able to improve their competence, attitudes and skills in order to get job opportunities. This training aims to explain the process of efforts to increase job opportunities through graphic design training. The results of the training show that the implementation of graphic design training has been going well, supported by maximum efforts at each stage of the training. In addition, aspects that need to be considered in graphic design training are also to obtain job opportunities, namely job information, training conditions and conditions of graphic design training graduates. Keywords: Digital Design Training, PKL, Job Opportunities.